NAVIGATING THE DIGITAL FRONTIER: A COMPREHENSIVE EXAMINATION OF COPYRIGHT PROTECTION IN THE DIGITAL ERA, UNRAVELING COMPLEX CHALLENGES, AND PROPOSING LEGAL SOLUTIONS - Loso Judijanto; Masruri; Nanang Zakaria; Eyad Saleh Bani-Domi; Iyad Abdallah Al- Shreifeen (Adisam Publisher, 2024)
This comprehensive exploration delves into the multifaceted realm of copyright protection within the digital era. In a landscape marked by rapid technological advancements, the study unravels intricate challenges existing copyright frameworks face and proposes nuanced legal solutions. The examination spans the borderless domain of cyberspace, where traditional copyright paradigms confront unprecedented complexities. Key themes include the global nature of digital environments, economic imperatives shaping intellectual property landscapes, and the dynamic interplay of technology and legal frameworks. The study navigates trademark issues in cyberspace, analyzes the impact of geodemographic systems, and scrutinizes legal instruments such as the European Directive on the protection of computer programs. By adopting a structured literature review methodology, the research extracts insights from diverse sources, offering a comprehensive understanding of the evolving dynamics. The exploration unfolds against the backdrop of a knowledge-based economy, emphasizing the pivotal role of copyright as the